Assessment of Radon Concentration in Blood Samples of Different Kinds of Cancer by Using CR-39 Nuclear Track Detectors - Sardar S. Othman; Zakariya A. Hussein; Najeba F. Salih (Zanco Journal of Pure and Applied Sciences, 2023)
The goal of this work to measure the radon concentrations in twenty blood samples taken from a cancer patient and a healthy group of Erbil governorates, by using CR-39 NTD. The results obtained the average concentrations of radon in blood samples for cancer patients and the healthy group were 19.318 ±3.86 Bq/m3 and 8.5077 ±1.84 Bq/m3 respectively. The mean value of radon concentration of the cancer group is higher than the healthy group. The variation in concentrations of radon in different locations may be caused due to the variation in the nature of blood samples and nuclei content in these samples. also depending on the allergic reaction of the body to radiation. This increase could be caused by pollution of environment with radioactive materials including uranium since cancer can be caused by ionization radiation results showed that the all of concentration of radon in blood samples for cancer and healthy group were less than the global permissibility limiting of exhibition to radon 200 Bq.m−3 (IAEA, 2010.)This work owes its importance to the fact that it aims at knowing and measuring the radon concentrations in the blood samples and impact it on the cancer in particular.